ANALISIS PENERAPAN SISTEM AKUNTANSI PENGGAJIAN DAN PENGUPAHAN DALAM UPAYA PENINGKATAN EFISIENSI BIAYA PADA UPT RS KUSTA LAU SIMOMO KABANJAHE - Br S Sidauruk, Claudy Octalia; Zahari, Zahari; Junaidi, Listya Devi (UNIVERSITAS DHARMAWANGSA, 2024)
The objective of this research is to determine the importance of implementing an effective payroll and wage accounting system in healthcare service organizations, such as the UPT RS Kusta Lau Simomo Kabanjahe, to improve operational cost efficiency. This research employs a qualitative descriptive approach, combining the analysis of primary data obtained through interviews and observations, as well as secondary data from financial reports and related documents. The findings of the study indicate that the implementation of a well-structured and standard-compliant payroll and wage accounting system can significantly reduce operational costs. The implications of this research suggest that the optimal implementation of such a system can serve as a critical strategy for managing budgets efficiently in healthcare institutions.